COMPETITIVE STRATEGY, MANAGEMENT ACCOUNTING SYSTEM INFORMATION AND CUSTOMER-RELATED PERFORMANCE - Sitiwati, Riana; Manaf, Sodikin; Sutono, Sutono; Budhiutama, Ngurah Arya Teguh (UI Scholars Hub, 2017)
This study aims to analyse how competitive strategy and managerial use of the management accounting system (MAS) information may affect customer-related performance in the hotel industry. An online survey involving 116 hotel general managers (GMs) was conducted to collect data from 3- to 5-star hotels located in Indonesia. Additionally, in-depth interviews with 19 GMs were performed in order to enhance the validity of the research findings and make the discussion of the results more informative. Based on the analysis, the results revealed that managerial use of MAS information may enhance customer-related performance in the hotel industry after competitive strategy has been applied. This paper provides empirical evidence on the relationship between competitive strategy, managerial use of MAS information, and customer-related performance of hotel industry in Indonesia.